Modern land management as a fundamental tool in providing the rational use and protection of land resources - Dobriak, D.; Zholobova, S. (Land Management, Cadastre and Land Monitoring, 2019)
The dynamics of the development of modern land management in the process of land reforming and the full implementation of land reform of the transformative processes as to restructuring of the land fund of Ukraine, as well as the creation of new land arrangements, which would provide for their development guided by the market principles were reasoned. As the result of the implementation of various activity types for land management in the field of land-reclamation management of the agricultural enterprises’ territory and establishment of an innovative form of ownership, other than a state, private, communal, thus launching a market-oriented land management was indeed necessary to significantly modify the true nature of the modern land management, in particular, to forego the sectoral one and to introduce the sharing principle for territorial reallocation of land: at the national, regional and local levels with further assignment the corresponding documentation on land management to each level. The mentioned land sharing was legally formalized in the provisions of the Law of Ukraine “On Land Management”. The implementation of other activities regarding the denationalization of lands, transformation of the existing structures of land management, establishment of farms, demarcation of land shares, implementation provided the formalization of leasing relationship and other types of procedural and institutional as well as normative-technical nature were implemented based on the schemes and layouts for land management and other documentation, having formed the basis for the implementation of the state land politics. Thus, the modern land management deems to be one of the fundamental tools needed for the implementation of the state regulatory policies as to the use and protection of lands, and, above all, agricultural ones. The role of modern land management in providing the ecologically safe and economically efficient use of land, particularly in the conditions of the development of degradation processes, and to a certain extent regulating social relations with respect to land ownership, use and disposal is considered. Its economic, environmental and social effectiveness is substantiated on a specific example. Key words: land management, land resources, economic, ecological, social efficiency, degradation processes.